Acute Kidney Injury Biomarkers and Hydration Outcomes at the Boston Marathon - Atkins, Whitley C.; Butts, Cory L.; Kelly, Melani R.; Troyanos, Chris; Laursen, R. Mark; Duckett, Andrew; Emerson, Dawn M.; Rosa-Caldwell, Megan E.; McDermott, Brendon P. (Frontiers in Physiology, 2022)
The purpose of our field study was to investigate the effects of running the Boston Marathon on acute kidney injury (AKI) biomarkers. We hypothesized that biomarker values would be elevated immediately post-marathon but would resolve in the 24-hrs post-marathon. Secondarily, we sought to identify sex differences related to renal stress. Participants were 65 runners who completed the Boston Marathon (46 ± 9 y, 65.4 ± 10.8 kg). Urine samples were collected at three different time points (pre-marathon, post-marathon, and 24-h post-marathon). Blood samples were collected post-marathon and 24-h post-marathon. Urine specific gravity (USG) and AKI biomarkers were evaluated. Pre-marathon USG (1.012 ± .007) was significantly less than post-marathon (1.018 ± .008) and 24-hr post-marathon (1.020 ± .009; P <.001). Male USG (1.024 ± .009) was significantly greater 24-hr post-marathon than females (1.017 ± .008; P =.019). Urinary neutrophil gelatinase-associated lipocalin values were significantly greater over time (P < .001), and there was a main effect of sex with female urinary creatinine (UCr) greater than males at all three times points (P = .040). Post-marathon UCr (366.24 ± 295.16 mg/dl) was significantly greater than pre-marathon (206.65 ± 145.28.56 mg/dl; p <.001) and 24-hr post-marathon was significantly lower than other time-points (93.90 ± 125.07 mg/dl; P < .001). Female uCr values were significantly greater than males 24-hr post-marathon, (P < .001). There was no difference in serum cystatin C (SCys) values post- or 24-hr post-marathon (P = .178). Serum creatinine (SCr) significantly decreased between post-marathon and 24-hr post-marathon, (P < .001). We can infer that the characteristics unique to the Boston Marathon may have attributed to prolonged elevations in AKI biomarkers. Sex differences were observed during the Boston Marathon warranting further investigation.